2011
DOI: 10.1136/ard.2010.143016
|View full text |Cite
|
Sign up to set email alerts
|

Erosive hand osteoarthritis: its prevalence and clinical impact in the general population and symptomatic hand osteoarthritis

Abstract: The prevalence of EOA is 2.8% in the general population and 10.2% in individuals with symptomatic HOA. It has a substantial impact on hand pain and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
0
19

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 29 publications
6
60
0
19
Order By: Relevance
“…The prevalence of symptomatic OA was 11%. Participants without erosive OA were statistically younger (66.1 ± 7 years) than those with erosive OA (68.6 ± 6.5 years) [3]. It seems that in our study, among the patients younger than 62, OA was more aggressive than in the population described by Kwok et al All patients were diagnosed OA according the American College of Rheumatology diagnosis criteria for OA of the hand edited in 1990 [4].…”
Section: Discussionmentioning
confidence: 82%
“…The prevalence of symptomatic OA was 11%. Participants without erosive OA were statistically younger (66.1 ± 7 years) than those with erosive OA (68.6 ± 6.5 years) [3]. It seems that in our study, among the patients younger than 62, OA was more aggressive than in the population described by Kwok et al All patients were diagnosed OA according the American College of Rheumatology diagnosis criteria for OA of the hand edited in 1990 [4].…”
Section: Discussionmentioning
confidence: 82%
“…Rotterdam çal›flmas›nda 55 yafl üzerindeki genel popülas-yonda interfalengeal eklemlerde EOA prevalans› %2.8 olarak tahmin edilmifltir. [73] 40 yafl üzeri 200 semptomatik el OA hastas›n› içeren bir çal›flma ile, 50 yafl üzeri 1076 hastay› içeren bir di¤er çal›flmada, EOA prevalans› s›ras›yla %7 ve %7.4 olarak saptanm›flt›r. [74,75] Daha yüksek prevalans oranlar› 2011 y›l›nda yap›lan Framingham çal›flmas›n-da bildirilmifl olup 40-80 yafl aras› yetiflkinlerde prevalans erkekler için %3.3, kad›nlar için %9.9 olarak bulunmufltur.…”
Section: Erosiv Osteoartritunclassified
“…[76] EOA kad›nlar› erkeklerden daha çok etkilemeye meyillidir; fakat Rotterdam çal›flmas›nda erkek ve kad›nlar aras›nda belirgin bir fark saptanmam›flt›r. [73] Eroziv lezyonlar bask›n olarak D‹F eklemlerde olup, daha az olarak da P‹F'lerde izlenmektedir. [76,77] Crain ve ark.…”
Section: Erosiv Osteoartritunclassified
See 1 more Smart Citation
“…Kwok et al 1 , reported the prevalence of erosive hand osteoarthritis to be 2.8% in the general population and 10.2% in individuals with symptomatic hand osteoarthritis 1 . They concluded it to have a profound impact on pain and disability in individuals over the age of 55 years 1 . Although it is difficult to predict future prevalence of this disease it is estimated that OA will be the leading cause of disability by the year 2020 2 .…”
Section: Introductionmentioning
confidence: 99%